Real-world treatment patterns, biomarker testing, and clinical outcomes of metastatic non-small cell lung cancer patients in the immunotherapy era - Apter, Lior; Sharman Moser, Sarah; Arunachalam, Ashwini; Gazit, Sivan; Hoshen, Moshe; Chodick, Gabriel; Siegelmann-Danieli, Nava (Frontiers in Oncology, 2024)
BackgroundTreatment for first-line (1L) metastatic non-small cell cancer (mNSCLC) changed with the introduction of immunotherapy. We describe treatment utilization and clinical outcomes in a real-world mNSCLC cohort in a 2.7-million-member state-mandated health provider.MethodsNewly diagnosed mNSCLC patients initiating systemic anti-cancer treatment (January 2017–December 2020) were identified from the National Cancer Registry. Real-world time on treatment (rwToT) was defined as the length of time between the first and last administration date of treatment. Real-world overall survival (rwOS) was estimated using Kaplan–Meier analysis. Outcomes were assessed at a minimum of 6 months’ follow-up (cutoff: 30 June 2021).ResultsAmong 843 patients, 85% had adenocarcinoma (NSQ) and 15% had squamous cell carcinoma (SQ) histology: of these, 43% and 26% were women, median age was 67 and 69 years, and 55% and 48% had 0–1 ECOG performance status, respectively (missing: 27% and 30%, respectively). Median follow-up for the entire cohort was 27.1 months (95% CI: 24.7–29.6). NSQ patients with no known EGFR/ALK/ROS1 aberrations received PD-1 inhibitor monotherapy (PDM) (N = 147) or combination (PDC) (N = 194) or platinum-based chemotherapy (PBC, N = 133). Median rwToT was 4.5 (95% CI: 3.5–7.6), 5.2 (95% CI: 4.6–7.6), and 2.3 (95% CI: 2.1–3.0) months, respectively; for the subgroup of patients with ECOG PS 0–1, rwToT was 9.4 (95% CI: 5.0–20.8), 7.1 (95% CI: 5.0–10.1), and 2.9 (95% CI: 2.2–4.1) months, respectively. Median rwOS from 1L was 12.5 (95% CI: 9.9–17.9), 14.8 (95% CI: 10.5–19.4), and 9.1 (95% CI: 7.1–11.5) months; for the subgroup of patients with ECOG PS 0–1, median rwOS was 25.1 [95% CI: 14.9–not reached (NR)], 17.6 (95% CI: 14.3–NR), and 11.3 (95% CI: 9.2–21.3) months, respectively. For ECOG PS 0–1 and PD-L1 ≥50% patients, median rwOS was 25.1 months (95% CI: 13.9–NR) and NR for PDM and PDC, respectively. For ECOG PS 0–1 and PD-L1 <50% patients, median rwOS was 14.3 (95% CI: 10.1–NR) and 11.2 (95% CI: 9.1–21.3) months for PDC and PBC, respectively.ConclusionOur real-world data support the benefit of single-agent PD-1 inhibitor monotherapy for patients with PD-L1 high expression or PD-1 inhibitor combination for all patients diagnosed with mNSCLC with no known EGFR/ALK/ROS1 aberrations, initiating 1L treatment.